2019
DOI: 10.1101/675249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A classification framework forBacillus anthracisdefined by global genomic structure

Abstract: Bacillus anthracis, the causative agent of anthrax, is a considerable global health threat affecting wildlife, livestock, and the general public. In this study whole-genome sequence analysis of over 350 B. anthracis isolates was used to establish a new high-resolution global genotyping framework that is both biogeographically informative, and compatible with multiple genomic assays. The data presented in this study shed new light on the diverse global dissemination of this species and indicate that many lineag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Whole genome sequencing is a powerful alternative method to MLVA, with the versatility to look at disease outbreak origins, introductions, and routine surveillance to support epidemiological investigations. This technology is becoming standard practice for examining the genetic diversity of clonal bacterial species such as B. anthracis [ 32 , 33 ]. Rapid classification frameworks made available by researchers such as Bruce et al [ 32 ] offer a simplified and robust tool for the analysis of B. anthracis evolution and classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole genome sequencing is a powerful alternative method to MLVA, with the versatility to look at disease outbreak origins, introductions, and routine surveillance to support epidemiological investigations. This technology is becoming standard practice for examining the genetic diversity of clonal bacterial species such as B. anthracis [ 32 , 33 ]. Rapid classification frameworks made available by researchers such as Bruce et al [ 32 ] offer a simplified and robust tool for the analysis of B. anthracis evolution and classification.…”
Section: Discussionmentioning
confidence: 99%
“…This technology is becoming standard practice for examining the genetic diversity of clonal bacterial species such as B. anthracis [ 32 , 33 ]. Rapid classification frameworks made available by researchers such as Bruce et al [ 32 ] offer a simplified and robust tool for the analysis of B. anthracis evolution and classification. Owing to the expansion of available genome sequence data and the comparison of B. anthracis strains worldwide [ 32 , 33 , 34 , 35 , 36 , 37 ], this approach offers greater insight into the global placement of the Australian strains and may provide a deeper understanding of the genomic diversity at a local level.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting phylogeny indicated that NCA isolates belong to the ancient A lineage. To further resolve the diversity among NCA isolates compared with other publicly available isolates from the same lineage, reads from eight additional isolates available from the Sequence Read Archive (SRA) from a study by Bruce et al [7] were accessed using Fastq-dump from the SRA-toolkit: all isolates (n=4) belonging to the 3.2 linage, and two arbitrarily selected isolates from each of the 3.1 and 3.3 lineages (Table S2). These were run through our SNP-calling pipeline as described above, resulting in a sequence alignment file free of -/N characters, which was used to infer a phylogeny in RAxML v8.2.11 [48] using a GTR (general time reversible) model of nucleotide substitution, and using the Ames Ancestor reference genome as an outgroup.…”
Section: Bioinformatics and Genomic Analysesmentioning
confidence: 99%
“…The genomic diversity of B. anthracis has been well-described at a global scale. Isolates can be broadly divided into three major clades (A, B, C), of which the A clade is the most widespread and globally dominant [5][6][7]. Isolates from most B. anthracis lineages have been found across geographically widespread areas, often spanning multiple continents [7].…”
Section: Introductionmentioning
confidence: 99%
“…An isolate was obtained from a blood swab from a zebra carcass containing the most common genotype in Etosha (genotype 6) according toBeyer et al (39). This isolate is from A.Br.003 (A.Br.Aust94) using Van Ert et al's(40) global classification, and group 5.4 using a new population genomic classification(41). The zebra carcass was found on 22 February 2010 (carcass ID: EB100224-01WT).…”
mentioning
confidence: 99%